An approach to the convent of Santa Clara de Asís in Havana. Study of its conservation status and intervention proposals - López, Jennifer; Acosta Toirac, Yasnay; Cazañas Marisy, Caridad María (Revista ALCONPAT, 2019)
Santa Clara de Asis Convent High Choir timber truss has been victim of humidity and attack of abiotic and biotic agents which have caused its gradual degradation. For the identification of pathological processes associated with these agents and because of its patrimonial character, a diagnosis study based on an organoleptic inspection and superficial tests was carried out with the available instruments, which allowed identifying the causes. By modeling the structure with SAP 2000 program, we obtained the results that were used to calculate the solutions proposed for the identified pathologies, mainly for the loss of connection between the wall plate and the tie rod beam.